2009
DOI: 10.1007/s12197-009-9089-z
|View full text |Cite
|
Sign up to set email alerts
|

Open interest, volume, and volatility: evidence from Taiwan futures markets

Abstract: Open Interest, Trading Volume, Volatility, VAR, GARCH, G15,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In summary, we incorporate an open interest variable into the HAR-RRV-RTV model in the present study, and claim that the modified model not only provides additional and useful information on volatility dynamics, but also better forecasting performance than the HAR-RRV-RTV model in terms of predicting the volatility for CSI 300 index futures. Finally, our findings are in line with Girma and Mougoue (2002) and Yen and Chen (2010), and support the implication of the SIA hypothesis.…”
Section: Robustness Checkssupporting
confidence: 89%
See 3 more Smart Citations
“…In summary, we incorporate an open interest variable into the HAR-RRV-RTV model in the present study, and claim that the modified model not only provides additional and useful information on volatility dynamics, but also better forecasting performance than the HAR-RRV-RTV model in terms of predicting the volatility for CSI 300 index futures. Finally, our findings are in line with Girma and Mougoue (2002) and Yen and Chen (2010), and support the implication of the SIA hypothesis.…”
Section: Robustness Checkssupporting
confidence: 89%
“…For example, Bessembinder and Seguin (1993) and Chan et al (2004) found that volatility was negatively related to open interest. In contrast, however, Liew and Brooks (1998) and Serletis and Shahmoradi (2006) suggested that a positive and statistically significant relationship existed between volatility and open interest (see also Yen and Chen 2010;Ripple and Moosa 2009;Shakeel and Ashraf 2012;Boonvorachote and Lakmas 2016). In the present study, we focus on the impact of open interest on realized volatility, in an attempt to improve futures volatility forecasting performance.…”
Section: Data Source and Empirical Resultsmentioning
confidence: 86%
See 2 more Smart Citations